Carrying Weapons or Sale to Minors Prohibited, Amendment to Ordinance No. 11-Crimes and Punishment, §§ 7-9 in Ordinances, Charter and Laws for the Government of the City of Frankfort, Kentucky (1876) - (:unkn) unknown (My University, 1876)
Prohibited discharge of any gun or pistol in the city unless in lawful defense. Also prohibited concealed carry of deadly weapons except ordinary pocket knives. Also prohibited selling deadly weapons to minors other than pocket knives.
Keywords: CARRY - CONCEALED; DISCHARGE; TRANSFER - MINORS